1984
DOI: 10.1071/ea9840034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different stocking intensities in early life on the productivity of Merino ewes grazed as adults at two stocking rates. 1. Wool production and quality, lamb growth rate, and size and liveweight of ewes

Abstract: Ewe lambs born to Merino ewes grazed at 10 or 20 sheep/ha were weaned at three months (L-, H-) and randomized to low or high stocking rate treatments (-L, -H) until 15 months old. Ewes from each of the four groups (LL, LH, HL and HH) then grazed at 10 or 20 sheep/ha until nine years old. Liveweight in early adult life and some body dimensions were reduced by a low plane of nutrition during rearing. The differences in liveweight declined with time and were not significant after 2% years in ewes stocked as adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Increasing stocking rate generally reduces FOO, wool growth and SL (White and McConchie, 1976;Brown, 1977;Langlands et al, 1984;Craig, 1992;Doyle et al, 1999) although in some studies measured SL was only reduced at the lowest FOO (Thompson et al, 1994). Doyle et al (1999) reported that strip grazing reduced SL compared with set stocking as both fleece growth and FD declined.…”
Section: Fibre Lengthmentioning
confidence: 94%
See 3 more Smart Citations
“…Increasing stocking rate generally reduces FOO, wool growth and SL (White and McConchie, 1976;Brown, 1977;Langlands et al, 1984;Craig, 1992;Doyle et al, 1999) although in some studies measured SL was only reduced at the lowest FOO (Thompson et al, 1994). Doyle et al (1999) reported that strip grazing reduced SL compared with set stocking as both fleece growth and FD declined.…”
Section: Fibre Lengthmentioning
confidence: 94%
“…At any point in time however, liveweight reflects both the long term effects of growth towards mature size, and the effects of short term seasonal changes in nutrition, typified in much of the wool growing regions of Australia by liveweight loss during periods of low pasture digestibility and availability and liveweight gain with the return of pastures with high digestibility. Such changes in liveweight are documented in multi-year studies of grazing sheep (White and McConchie, 1976;Brown, 1977;Black and Reis, 1979;Langlands et al, 1984;Craig, 1992;McGregor, 2010). Thus it is not possible to separate the effects of nutrition on wool growth and quality from the effects of nutrition on the liveweight of sheep.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is generally contended that as stocking rate is increased, Merino wool production per unit area will increase proportionately (Chisholm 1965;Blackburn et al 1973). Although Merino wool quality may be reduced somewhat at high stocking rates (Langlands et al 1984), it is clear that stock numbers will strongly influence the income from high country runs.…”
Section: Introductionmentioning
confidence: 99%